International prosecution of human rights crimes - Kaleck, Wolfgang; Ratner, Michael; Singelnstein, Tobias; Weiss, Peter (Springer, 2007)
The book explores recent developments in the international and national prosecution of persons accused of committing war crimes and crimes against humanity